A Business Analysis of Asian Baseball Leagues. (January 2016) - Jang, Hayley; Lee, Young Hoon
Abstract : This study reviews previous research on sports economics and applied descriptive analyses to derive policy recommendations for the Korean Baseball Organization and the Nippon Professional Baseball. We discuss various aspects of the contemporary baseball business, and compare them with the American Major League Baseball (MLB). One distinctive characteristic common to both Asian leagues is the governance structure, where member teams are owned by major conglomerates. We explore this characteristic to assess the business objectives of the Korean Baseball Organization and the Nippon Professional Baseball, and find that their sources of competitive balance differ from those in MLB. Our conclusion suggests that their business objective should begin to move slowly toward one similar to that of MLB, and safeguards should be implemented to maintain a reasonable competitive balance. We also conclude that sports diplomacy and the creation of international competition are important because international competition and the success of national teams are critical for fan demand.